2001
DOI: 10.1023/a:1010707417274
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Autism is a developmental disorder marked by impairments in socialization, communication, and perseverative behavior and is associated with cognitive impairment and deficits in adaptive functioning. Research has consistently demonstrated that children with autism have deficits in adaptive functioning more severe than their cognitive deficits. This study investigates the correlates and predictors of adaptive functioning as measured by the Vineland Adaptive Behavior Scales in high- and low-functioning children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

18
102
6
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 276 publications
(127 citation statements)
references
References 12 publications
18
102
6
1
Order By: Relevance
“…The analyses build upon existing research that has reported on the relationship between cognitive and adaptive levels (e.g., Bolte and Poustka 2002), examined profiles on the VABS within samples with autism (e.g., Carter et al 1998), compared VABS scores for individuals with autism to those of other diagnostic groups (e.g., Volkmar et al 1987), and reported on the relationship among adaptive functioning, developmental level, and severity of autism symptomatology in individuals with ASD (e.g., Liss et al 2001). …”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The analyses build upon existing research that has reported on the relationship between cognitive and adaptive levels (e.g., Bolte and Poustka 2002), examined profiles on the VABS within samples with autism (e.g., Carter et al 1998), compared VABS scores for individuals with autism to those of other diagnostic groups (e.g., Volkmar et al 1987), and reported on the relationship among adaptive functioning, developmental level, and severity of autism symptomatology in individuals with ASD (e.g., Liss et al 2001). …”
mentioning
confidence: 99%
“…It has generally been found that cognitive and adaptive composite scores are highly correlated (e.g., Liss et al 2001;Vig and Jedrysek 1995) but also that overall adaptive functioning is lower than cognitive level, at least for higher functioning people with ASD (e.g. Bolte and Poustka 2002;Freeman et al 1991;Klin et al 2007).…”
mentioning
confidence: 99%
See 3 more Smart Citations